Repeated Sprints in Fasted State Impair Reaction Time Performance. (3rd April 2017) - Cherif, Anissa; Meeusen, Romain; Farooq, Abdulaziz; Briki, Walid; Fenneni, Mohamed Amine; Chamari, Karim; Roelands, Bart
ABSTRACT: Objective : The aim of this study was to assess the effects of 3-day Islamic intermittent fasting (3d-IF) on cognitive performance and serum levels of neurotrophic factors (brain-derived neurotrophic factor [BDNF] and vascular endothelial growth factor [VEGF]) before and after repeated sprints. Methods : Twenty-one physically active male Muslims (29.8 ± 5.9 years, exercising 4 ± 1.5 times/week) were randomly assigned to one of 2 experimental sessions: the control or nonfasting session (CS) or the fasting session (FS). These 2 sessions occurred 7 days apart in a counterbalanced crossover design. In both conditions, the test was performed at the same time of day, approximately 1 hour before sunset. In the FS, the test occurred on the third day of the 3d-IF and involved the participants' performance of the following: (a) two series of 5 maximal 5-second sprints and (b) 2 cognitive tasks: One Touch Stockings (OTS) and reaction time (simple and complex RTI). Results : In both conditions, the participants' reaction times during the RTI test were similar at the pre- and mid-exercise points, but postexercise, simple and complex reaction times were higher in FS compared to CS ( p = 0.045, effect size [ES] = 0.21 and p = 0.006, ES = 0.41, respectively). However, OTS performance and serum levels of neurotrophic factors were not influenced by the 3d-IF. Conclusion : Simple and complex reaction times during the RTI test were negatively affected by the 3d-IF after 2 bouts of intensive repeated sprints.